Keanekaragaman diatom epilitik sebagai bioindikator kualitas air sungai: studi kasus di coban tarzan, kabupaten malang - Laksono, Tomi (Maliki Interdisciplinary Journal, 2025)
The diversity of epilithic diatoms serves as a significant biological indicator for assessing river water quality. This study aims to examine the diversity of epilithic diatoms and evaluate their potential as bioindicators of water quality in the Coban Tarzan stream, Malang Regency. Sampling was conducted using a purposive sampling method at three stations characterized by different anthropogenic activities: upstream waterfall area, agricultural zone, and tourist site. Diatoms were identified based on frustule morphology and analyzed using the Shannon-Wiener Diversity Index (H’), Simpson Dominance Index (C), and the Trophic Diatom Index (TDI). Results showed a total epilithic diatom density of 152,669 ind/cm² with eight genera identified, including Navicula, Gomphonema and Rhoicosphenia as dominant genera. The diversity index (H’ = 1.52) indicated a moderate level of diversity, while the dominance index (C = 0.25) suggested no single species dominance. The TDI values ranged from 53.27 to 55.17, classifying the water quality as mesotrophic or moderately polluted. These findings confirm that epilithic diatom communities have strong potential as effective bioindicators for monitoring the impact of human activities on riverine water quality